2020
DOI: 10.3390/ani10030380
|View full text |Cite
|
Sign up to set email alerts
|

Ovulatory Response of Weaned Sows to an Altered Ratio of Exogenous Gonadotrophins

Abstract: At weaning, 33 mixed parity Hypor sows received either an injection of 400 IU equine chorionic gonadotrophin and 200 IU human chorionic gonadotrophin (hCG) (PG600; n = 13), PG600 with an additional 200 IU hCG 24 h later (Gn800; n = 11), or served as non-injected controls (n = 9). All gonadotrophin treated sows received an injection of 750 IU hCG at 80 h after weaning to induce ovulation (designated as time 0 h). At 0, 24, 36, 40, 44, 48, and 60 h, all sows were subject to transrectal ultrasonography to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Whether the preovulatory follicle diameters and the weaning-toovulation intervals in spontaneously ovulating hyperprolific sows are associated with their backfat thickness at weaning and their parity have not been investigated under tropical conditions. Pearodwong et al ( 2019) demonstrated that sows with low backfat thickness at weaning showed a delayed GnRH administration-to-ovulation interval, which mirrors other research indicating hCG treatment accelerated ovulation in sows (Manjarín et al, 2020). Likewise, weaned sows with poor body condition scores showed delayed estrogenic-toovulation intervals (Pearodwong et al, 2019).…”
Section: Gestation and Lactation Managementmentioning
confidence: 88%
“…Whether the preovulatory follicle diameters and the weaning-toovulation intervals in spontaneously ovulating hyperprolific sows are associated with their backfat thickness at weaning and their parity have not been investigated under tropical conditions. Pearodwong et al ( 2019) demonstrated that sows with low backfat thickness at weaning showed a delayed GnRH administration-to-ovulation interval, which mirrors other research indicating hCG treatment accelerated ovulation in sows (Manjarín et al, 2020). Likewise, weaned sows with poor body condition scores showed delayed estrogenic-toovulation intervals (Pearodwong et al, 2019).…”
Section: Gestation and Lactation Managementmentioning
confidence: 88%